Effect of nano silica (SiO2) on the hydration kinetics of cement - Abu-Lebdeh, Taher (Array, 2019)
This study investigated the influence of adding nano silica (SiO2) on the cement hydration process, particularly on the formation of calcium silicate hydrate (C-S-H) at different stages of hydration. The study investigated the effect of adding nano-silica on the mechanical properties of the hardened cement corresponding to the formation of C-S-H during the hydration process of a cement paste. Specimens made up of four different percentage of nano silica (0%, 1%, 3% and 5%) were tested at different stages of hydration ranging from 3 to 56 days. The effect of nano-silica on the compressive strength, stressstrain, and elastic modulus of nano-cement was examined using MTS and Forney testing machines. The signature phase and formation of C-S-H and calcium hydroxide (CH) were monitored using Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). The study also investigated the effect of curing method (vacuum and water curing) on the strength development. The experimental results show that the formation of calcium silicate hydrate (C-S-H) increases significantly during the early stages of hydration which correspond to the drastic increase in compressive strength. The formation of C-S-H continues to increase throughout the 56 days but at a moderate rate. The results reveal that 1% of nano silica by volume of cement is the optimum ratio that yields the maximum strength. The results also indicated that the strength of the traditional water cured specimens were higher than that of vacuum cured specimens.